Formation, activities and current situation of the Udi community in the Republic of Armenia - Ayvazyan , Grigori (History and Culture, 2025)
Some of the Udis refugees from Azerbaijan 1988-1990 settled in Armenia, mainly in the Tavush region in Noyemberyan, Debetavan, Haghtanak, Ptghavan, Bagratashen, Hakhtanak and other settlements. The Udis also settled in the city of Yerevan, in the Gegharkunik, Kotayk regions, etc. The number of ethnic Udis in different regions of the Republic of Armenia can range from about 200-500 to 1000-1500 people. There are many crypto-Udis in Armenia, which makes it difficult to determine their exact number. In 2018, an initiative group of the Udis of Armenia created the Udi public organization «Revival of the Udi People of Historical Albania». The main goals and objectives of the Udi community of the Republic of Armenia are as follows: 1) Study and popularization of the Udi language; 2) study of Udi history, 3) culture; 4) preserving the rituals, customs and traditions of the Udins in Armenia. During its existence in 2018-2024, the organization has already held a number of cultural and educational events. In the near future, the community is planning a number of other events. The Albanian-Udi community of Armenia closely cooperates with Armenian Caucasian scholars in order to develop and strengthen the centuries-old fraternal relations between the Udi and Armenian peoples.